Materiality in Modernist Short Fiction Lived Things - Oulanne, Laura (Among the Victorians and Modernists, 2021)
Materiality in Modernist Short Fiction provides a fresh approach to reading material things in modern fiction, accounting for the interplay of the material and the cultural. This volume investigates how Djuna Barnes, Katherine Mansfield, and Jean Rhys use the short story form to evoke the material world as both living and lived, and how the spaces they create for challenging gendered social norms can also be nonanthropocentric spaces for encounters between the human and the nonhuman. Using the unique knowledge created by literary works to spark new conversations between phenomenology, cognitive studies, and new materialisms, complemented with a feminist perspective, this book explores how literature can touch the basic experience of being in, feeling and making sense of a material world that is itself alive and active. From a sensitive reading of how three women used the material world to make their readers see, feel, and question the norms shaping our experience, this volume draws a theory of reading affective materiality that illuminates modernism and the short story form but also reaches beyond them.